Development of Teaching Materials Linear Program based on Problem-Based Learning Assisted by Geogebra Applications - Arisman Zebua; Asep Ikin Sugandi; Jozua Sabandar (IKIP Siliwangi, 2023)
This study aims to develop teaching materials for linear programming based on Problem Based Learning assisted by GeoGebra applications that are valid, practical, and effective. The type of research used is a type of development research using the 4-D development model. The 4-D development model consists of the Define, design, develop, and disseminate phases. This study only reached the development stage. The research subjects were class XI SMA Negeri 2 Toma students. The instruments used were material expert and media expert validation sheets as well as student response practicality sheets and mathematical problem-solving ability tests. Based on the results of the research that has been done, it is found that the analysis of the validation results of material experts is 3.65 with a percentage of 73.06% in the valid category, and media expert validation is 4.08 with a percentage of 81.67% in the valid category. In the limited test, analysis of the results of the practicality sheet of 10 students obtained an average percentage of 73.73% in the practical category, and in the broad test of 29 students obtained an average percentage of 89.33% in the very practical category. In the effectiveness test, it was found that 71.25% was in good category. Thus, it can be concluded that the linear program teaching materials based on problem-based learning assisted by the GeoGebra application meet valid and practical criteria and are suitable for use in learning, and can be effective in facilitating mathematical problem-solving skills.